Interplay between U2 snRNP and 3' splice factor(s) for branch point selection on human beta-globin pre-mRNA. - Alibert, C (1990)
We investigated the interaction of U2 snRNP with the branch-3' splice site region of three human beta-globin pre-mRNAs carrying nearly complete (BamHI RNA), 24 nt (Avall RNA) and 14 nt (Accl RNA) of exon 2. All supported splicing, but mRNAs yields were respectively 2 and 10 times lower for Avall and Accl RNAs than for BamHI. Analysis of RNase T1-resistant fragments immunoprecipitated by an anti-(U2)RNP antibody at early times of the splicing reaction showed that the protection encompasses both the branch point region and the end of the intron in BamHI and Avall, but essentially only the branch point in Accl RNAs. Later on, this protection becomes less detectable in BamHI, is reinforced in Avall and remains poorly detectable in Accl RNAs. Similar experiments performed at late times with an anti-Sm antibody recognizing all snRNPs showed that the end of the intron is protected in all but BamHI RNAs. These results support the conclusion that U2 snRNP binds to a fully efficient precursor (BamHI RNA) through another factor(s) recognizing the 3' splice site (U5 snRNP and the so-called U2AF protein are likely candidates). Either the absence of an initial contact between U2 snRNP and the factor(s) recognizing the end of the intron (Accl RNA) or the unability of this ternary complex to undergo a conformational change (Avall RNA) could render these severely truncated precursors poor substrates. These different situations have consequences on the branch point selection itself. BamHI and Avall RNAs use three functional branch points at early times, the usual A residue at -37 and two U residues at -17 and -22. Accl RNA uses only one branch point at -37. Later on, all three branch points are used at the same rate in Avall, while the usual one prevails in BamHI RNAs.